(3JaYjd GdJShjb GdeUQaj dehGLgI BKGQ GdLGJSs - (3CMeO eQGO(B, (3SGeis ((3GdbGgQI(B:s (3GdecJH GdYQHj ddeYGQa,s, 2007)
(3jVe GdLGJS hGdNOeGJ GdeUQajI, GdJShjb GdeUQaj hOQGSI GdYedGA hGdShb, JaYjd GdJShjb GdeUQaj hJMbjb QVG GdYejd, GOGQI GdfTGW GdJShjbj aj GdHfcs
(3HjHdjhZQGajG(B: (3U(B.297s
Keywords: (3GdGOGQIs; (3GdHfhcs; (3GdJShjbs